Development of a four-dimensional Monte Carlo dose calculation system for real-time tumor-tracking irradiation with a gimbaled X-ray head. (March 2017) - Ishihara, Yoshitomo; Nakamura, Mitsuhiro; Miyabe, Yuki; Mukumoto, Nobutaka; Matsuo, Yukinori; Sawada, Akira; Kokubo, Masaki; Mizowaki, Takashi; Hiraoka, Masahiro
Highlights: A 4D dose calculation system for real-time tumor tracking (RTTT) was developed. A 6-MV photon beam delivered by the Vero4DRT was simulated using EGSnrc. Differences between the simulated and measured doses were less than 3% for RTTT. Target coverage in RTTT plans was almost identical to that of the non-RTTT plans. Our system helps predicting intrafraction variations in the dose distributions. Abstract: Purpose: To develop a four-dimensional (4D) dose calculation system for real-time tumor tracking (RTTT) irradiation by the Vero4DRT. Methods: First, a 6-MV photon beam delivered by the Vero4DRT was simulated using EGSnrc. A moving phantom position was directly measured by a laser displacement gauge. The pan and tilt angles, monitor units, and the indexing time indicating the phantom position were also extracted from a log file. Next, phase space data at any angle were created from both the log file and particle data under the dynamic multileaf collimator. Irradiation both with and without RTTT, with the phantom moving, were simulated using several treatment field sizes. Each was compared with the corresponding measurement using films. Finally, dose calculation for each computed tomography dataset of 10 respiratory phases with the X-ray head rotated was performed to simulate the RTTT irradiation (4D plan) for lung, liver, and pancreatic cancer patients. Dose-volume histograms of the 4D plan were compared with those calculated on the single reference respiratory phase without the gimbal rotation [three-dimensional (3D) plan]. Results: Differences between the simulated and measured doses were less than 3% for RTTT irradiation in most areas, except the high-dose gradient. For clinical cases, the target coverage in 4D plans was almost identical to that of the 3D plans. However, the doses to organs at risk in the 4D plans varied at intermediate- and low-dose levels. Conclusions: Our proposed system has acceptable accuracy for RTTT irradiation in the Vero4DRT and is capable of simulating clinical RTTT plans.